A brightness enhancement film capable of preventing adsorption and improving brightness and a preparation method thereof
By designing a brightening film structure including a prism layer, a substrate layer and a backcoat layer, using the prism-shaped and hemispherical microstructure and fine sand structure, the problem of the brightening film drop due to electrostatic adsorption is solved, and the brightening film is achieved. Anti-adsorption and brightness enhancement effects.
Patent Information
- Application Number
- CN202111498423.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-09
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-12-09
AI Technical Summary
In use, existing brightening films are prone to decrease in brightness due to electrostatic adsorption, and their structure is complex and difficult to simplify.
A brightening film that prevents adsorption and increases luminance is designed. The structure includes a prism layer, a substrate layer and a back coating from top to bottom. The prism layer is equipped with a periodic arrangement of prism structure, and the back coating is evenly distributed on the back coating. There are hemispherical microstructures and pedal-shaped microstructures, with gaps filled with fine sand structures and diffused particles.
By replacing the rough surface of the back coating by the prism-shaped microstructure, the hemispherical microstructure prevents adhesion and fine sand structures diffuse light, the anti-adsorption and brightness of the brightening film are achieved, simplifying the structure and eliminating the lower prism film.
Smart Images

Figure CN114114487B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of brightness enhancement films, and in particular to a brightness enhancement film capable of preventing adsorption and improving brightness and a preparation method thereof. Background Art
[0002] Generally, brightness enhancement films are often used in combination with other films in practical applications. For example, two prism sheets overlap orthogonally in the prism direction, and the prism structure of one prism sheet contacts the smooth surface of the other prism. Because the back coating is a smooth surface, static electricity will be generated when they are put together, and they will be adsorbed together, resulting in no gaps between the films, and light cannot be reflected, which reduces the brightness of the entire product.
[0003] The existing brightness enhancement films have the following problems: 1. The brightness enhancement films currently used in televisions are basically two layers superimposed at an angle, and the prism surface and the smooth surface are more likely to produce adsorption; 2. The superposition of the back coating of the brightness enhancement film and the prism layer generates static electricity, which leads to adsorption and easily reduces the overall brightness. Summary of the invention
[0004] The present invention aims at the defects in the prior art such as the easy adsorption of the back coating layer and the prism layer, and provides a new brightness enhancement film which can prevent adsorption and improve brightness, and a preparation method thereof.
[0005] In order to solve the above technical problems, the present invention is implemented by the following technical solutions:
[0006] A brightness enhancement film that prevents adsorption and improves brightness comprises, from top to bottom, a prism layer, a substrate layer, and a back coating layer connected in sequence, the prism layer being provided with a periodically arranged prism structure, the back coating layer being evenly distributed with hemispherical microstructures, prism-shaped microstructures being provided between adjacent hemispherical microstructures, the side surfaces of the prism-shaped microstructures being tangent to the side surfaces of the hemispherical microstructures, the height of the prism-shaped microstructures being smaller than the height of the hemispherical microstructures, gaps being left between the prism-shaped microstructures and the hemispherical microstructures and being filled with fine sand structures, the fine sand structures being evenly distributed with diffused particles having a particle size of 3 to 5 μm.
[0007] In the above-mentioned anti-adsorption and brightness-enhancing brightening film structure, the prism-shaped microstructure has a shape similar to the prism structure, and can also play the role of focusing light and improving brightness, thereby replacing the conventional back-coated rough surface in the prior art; the hemispherical microstructure has the effect of preventing adhesion, and the fine sand structure can diffuse and atomize the light reflected, refracted, and scattered in the prism-shaped microstructure and the hemispherical microstructure, and play a role of reuse, further improving the overall brightness of the brightening film. The existing conventional brightening module usually has two prism films, and the present invention makes a prism-shaped microstructure under the prism layer to simulate the effect of the lower prism film in the existing brightening module, thereby eliminating the lower prism film and greatly simplifying the structure of the brightening module. The present invention achieves the effect of POP prism-prism composite film through the structure of only one prism film, which not only overcomes the defects of the prior art, but also has outstanding substantive characteristics and significant progress.
[0008] Preferably, in the above-mentioned anti-adsorption and brightness-enhancing brightness enhancing film, the height of the hemispherical microstructure is 15 to 20 μm, the height of the prism-shaped microstructure is 10 to 12 μm, the width pitch4 of the hemispherical microstructure is 10 to 15 μm, the bottom width pitch3 of the prism-shaped microstructure is 6 to 10 μm, and the top width pitch2 is 3 to 5 μm.
[0009] In the present invention, the height of the hemispherical microstructure is greater than that of the prism-shaped microstructure, so that the convex arc portion of the hemispherical microstructure can have a significant anti-adhesion effect, and the top of the prism-shaped microstructure is smaller than the bottom, and can serve as a lower prism to focus light.
[0010] Preferably, in the above-mentioned anti-adsorption and brightness-enhancing brightness enhancing film, the prism structure consists of high prisms and low prisms and is arranged in a high-N-low period, N≥1, the height of the high prisms is 30-35μm, and the height ratio t of the high prisms and the low prisms is 1<t≤1.25.
[0011] The prism structure of the present invention adopts a high-N low periodic arrangement, which can prevent interference and moiré, and also prevent adsorption with other upper film sheets.
[0012] Preferably, in the above-mentioned brightness enhancement film for preventing adsorption and improving brightness, N=3, and the pitch pitch1 between adjacent prism structures is 45-60 μm.
[0013] The present invention adopts a prism period of one high and three lows, which can ensure that the brightness enhancement film has sufficient brightness and also prevent it from being adsorbed with other upper diffusion films or polarizer films.
[0014] Preferably, the method for preparing the above-mentioned brightness enhancement film that prevents adsorption and improves brightness comprises the following preparation steps:
[0015] Q1: Take a copper or nickel roller blank A, use a diamond or diamond tool to carve a microstructure texture that matches the one high and three low prism structure on the roller blank A to make a prism roller;
[0016] Q2: Take a substrate layer and prism glue, evenly coat the prism glue on the substrate layer by a coating machine, and then prepare a prism layer on the upper surface of the substrate layer by combining a prism roller and UV embossing molding;
[0017] Q3: Take a copper or nickel roller blank B, and use a diamond or diamond tool to carve a composite microstructure texture that matches the hemispherical microstructure and the prism-shaped microstructure on the roller blank B to obtain a composite microstructure roller;
[0018] Q4: Take acrylic resin back coating, and prepare hemispherical microstructure and prism-shaped microstructure on the lower surface of the substrate layer by a composite microstructure roller and transfer process;
[0019] Q5: Take diffusion particles, acrylic resin, ethyl acetate, butyl acetate, curing agent, and leveling agent in a weight ratio of 0.5:1-2:2-3:2-3:0.1-0.2:0.2-0.3, mix them, stir them evenly to obtain fine sand glue, spray the fine sand glue into the gap between the hemispherical microstructure and the prism-shaped microstructure, and then combine the micro-concave scraper coating method to make the diffusion particles evenly distributed in the gap, and obtain the fine sand structure through UV curing or thermal curing, thereby completing the preparation of the back coating.
[0020] The copper or nickel roller blank A of the present invention can effectively completely separate the prism structure formed by the prism glue by rolling stripping. The present invention uses a diamond or diamond knife for engraving, which can ensure that the accuracy of the prism structure is controlled within ±0.5um.
[0021] In the above step Q2, the present invention adopts UV embossing, which can achieve instant curing and reduce the emission of harmful gases; through the combination of ultra-precision coater and roller hard pressing, the obtained prism layer structure has excellent thickness uniformity.
[0022] In the above step Q4, the curing method of the acrylic resin back coating is the same as the UV curing method in step Q2. The back coating is preferably a resin with a refractive index of 1.53 to 1.55, so as to obtain a structure consistent with the prism layer to achieve the effect of improving brightness.
[0023] In the above step Q5, the diffusion particles and acrylic resin in the fine sand structure can diffuse and atomize the light reflected, refracted and scattered in the prism-shaped microstructure and the hemispherical microstructure, and reuse them, thereby further improving the brightness. The present invention then uses a micro-concave scraper coating method to ensure thickness uniformity. The thermal curing process can fully release the internal stress of the product, and the warping and film arch performance of the product are guaranteed. UV curing has high curing efficiency and high dimensional accuracy of the product.
[0024] Preferably, in the above-mentioned method for preparing a brightness enhancement film that prevents adsorption and improves brightness, during the UV embossing process of step Q2, the energy of the UV lamp is controlled at 50-100 mj / cm 2 .
[0025] In the present invention, the curing energy of the UV lamp is controlled within the above range, so that the yellowing index of the surface of the prism product can meet the national standard, and at the same time, the warping and film arching caused by high temperature of the prism structure under high-energy irradiation can be avoided.
[0026] Preferably, in the above-mentioned method for preparing a brightness enhancement film that prevents adsorption and improves brightness, the prism-shaped microstructure is one of a quadrangular pyramid, a hexagonal pyramid, and an octagonal pyramid.
[0027] Prism-shaped microstructures are generally polygonal, which can gather light. At the same time, the light can also change its direction through multiple reflections and refractions inside, playing a focusing role. Part of the light enters the fine sand structure and is reused through the re-atomization of the diffusion particles, further enhancing the brightness and haze.
[0028] Preferably, in the above-mentioned method for preparing a brightness enhancement film that prevents adsorption and improves brightness, the diffusion particles are one of PMMA particles, PBMA particles, and acrylic glass beads.
[0029] The present invention preferably uses diffusion particles of the above-mentioned material, which are spherical in shape and can evenly atomize light to form diffuse light sources at multiple angles, thereby achieving multi-directional scattering of unidirectional light and having the effect of light reuse.
[0030] Preferably, in the above-mentioned method for preparing a brightness enhancing film that prevents adsorption and improves brightness, the substrate layer is PET, and the thickness of PET is 188-250 μm.
[0031] The present invention preferably uses PET with a thickness of 188 to 250 um, so that a high-stiffness product can be produced, the film arch and warping phenomena can be avoided, and the difficulty of coating production can also be reduced.
[0032] Preferably, in the above-mentioned method for preparing a brightness enhancement film that prevents adsorption and improves brightness, the refractive index of the prism layer is 1.55, and the prism structure presents a sinusoidal oscillation along the length direction of the top angle edge with an amplitude of 1.5 μm.
[0033] The refractive index of the prism layer of the present invention is controlled at 1.55, which can meet the cost and brightness requirements of customers, and the refractive index of this value is generally accepted at home and abroad. The prism structure presents a sinusoidal wave along the length direction of the top angle edge, further solving the problem that the existing prism layer is prone to interference. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a structural schematic diagram of the present invention;
[0035] Figure 2 It is a schematic structural diagram of the prism structure along the length direction of the top corner edge in the present invention. DETAILED DESCRIPTION
[0036] The following is combined with Figure 1-2 The present invention is further described in detail with specific embodiments, but they are not limitations of the present invention:
[0037] Example 1
[0038] A brightness enhancement film that prevents adsorption and improves brightness, comprising, from top to bottom, a prism layer 1, a substrate layer 2, and a back coating layer 3 connected in sequence, the prism layer 1 being provided with a periodically arranged prism structure 11, the back coating layer 3 being evenly distributed with hemispherical microstructures 31, prism-shaped microstructures 32 being provided between adjacent hemispherical microstructures 31, the side surfaces of the prism-shaped microstructures 32 being tangent to the side surfaces of the hemispherical microstructures 31, the height of the prism-shaped microstructures 32 being less than the height of the hemispherical microstructures 31, a gap being left between the prism-shaped microstructures 32 and the hemispherical microstructures 31 and being filled with a fine sand structure 33, the fine sand structure 33 being evenly distributed with diffused particles with a particle size of 3 μm.
[0039] Preferably, the height of the hemispherical microstructure 31 is 15 μm, the height of the prism-shaped microstructure 32 is 10 μm, the width pitch4 of the hemispherical microstructure 31 is 10 μm, the bottom width pitch3 of the prism-shaped microstructure 32 is 6 μm, and the top width pitch2 is 3 μm.
[0040] Preferably, the prism structure 11 is composed of high prisms and low prisms and arranged in a period of high to N low, where N≥1, the height of the high prisms is 30 μm, and the height ratio t of the high prisms to the low prisms is 1<t≤1.25.
[0041] Preferably, N=3, and the pitch pitch1 between adjacent prism structures 11 is 45 μm.
[0042] Preferably, the method comprises the following preparation steps:
[0043] Q1: Take a copper or nickel roller blank A, use a diamond or diamond tool to carve a microstructure texture that matches the one high and three low prism structure on the roller blank A to make a prism roller;
[0044] Q2: Take the substrate layer 2 and the prism glue, and evenly coat the prism glue on the substrate layer 2 by a coating machine, and then combine the prism roller and UV embossing molding to obtain the prism layer 1 on the upper surface of the substrate layer 2;
[0045] Q3: Take a copper or nickel roller blank B, and use a diamond or diamond tool to carve a composite microstructure texture that matches the hemispherical microstructure 31 and the prism-shaped microstructure 32 on the roller blank B to obtain a composite microstructure roller;
[0046] Q4: Take acrylic resin back coating glue, and prepare hemispherical microstructure 31 and prism-shaped microstructure 32 on the lower surface of the substrate layer 2 by composite microstructure roller and transfer process;
[0047] Q5: Take diffusion particles, acrylic resin, ethyl acetate, butyl acetate, curing agent, and leveling agent in a weight ratio of 0.5:1:2:2:0.1:0.2, mix them, stir them evenly to obtain fine sand glue, and then spray the fine sand glue into the gap between the hemispherical microstructure 31 and the prism-shaped microstructure 32, and then combine the micro-concave scraper coating method to make the diffusion particles evenly distributed in the gap, and obtain the fine sand structure 33 by UV curing or thermal curing, thereby completing the preparation of the back coating 3.
[0048] Preferably, during the UV embossing process in step Q2, the energy of the UV lamp is controlled at 50 mj / cm 2 .
[0049] Preferably, the pyramid-shaped microstructure 32 is one of a quadrangular pyramid, a hexagonal pyramid and an octagonal pyramid.
[0050] Preferably, the diffusion particles are one of PMMA particles, PBMA particles, and acrylic glass beads.
[0051] Preferably, the substrate layer 2 is PET, and the thickness of PET is 188 μm.
[0052] Preferably, the refractive index of the prism layer 1 is 1.55, and the prism structure 11 presents sinusoidal fluctuations along the length direction of the top corner edge, with an amplitude of 1.5 μm.
[0053] Example 2
[0054] A brightness enhancement film that prevents adsorption and improves brightness, comprising, from top to bottom, a prism layer 1, a substrate layer 2, and a back coating layer 3 connected in sequence, the prism layer 1 being provided with a periodically arranged prism structure 11, the back coating layer 3 being evenly distributed with hemispherical microstructures 31, prism-shaped microstructures 32 being provided between adjacent hemispherical microstructures 31, the side surfaces of the prism-shaped microstructures 32 being tangent to the side surfaces of the hemispherical microstructures 31, the height of the prism-shaped microstructures 32 being less than the height of the hemispherical microstructures 31, a gap being left between the prism-shaped microstructures 32 and the hemispherical microstructures 31 and being filled with a fine sand structure 33, the fine sand structure 33 being evenly distributed with diffused particles with a particle size of 5 μm.
[0055] Preferably, the height of the hemispherical microstructure 31 is 20 μm, the height of the prism-shaped microstructure 32 is 12 μm, the width pitch4 of the hemispherical microstructure 31 is 15 μm, the bottom width pitch3 of the prism-shaped microstructure 32 is 10 μm, and the top width pitch2 is 5 μm.
[0056] Preferably, the prism structure 11 is composed of high prisms and low prisms and arranged in a period of high to N low, where N≥1, the height of the high prisms is 35 μm, and the height ratio t of the high prisms to the low prisms is 1<t≤1.25.
[0057] Preferably, N=3, and the pitch pitch1 between adjacent prism structures 11 is 60 μm.
[0058] Preferably, the method comprises the following preparation steps:
[0059] Q1: Take a copper or nickel roller blank A, use a diamond or diamond tool to carve a microstructure texture that matches the one high and three low prism structure on the roller blank A to make a prism roller;
[0060] Q2: Take the substrate layer 2 and the prism glue, and evenly coat the prism glue on the substrate layer 2 by a coating machine, and then combine the prism roller and UV embossing molding to obtain the prism layer 1 on the upper surface of the substrate layer 2;
[0061] Q3: Take a copper or nickel roller blank B, and use a diamond or diamond tool to carve a composite microstructure texture that matches the hemispherical microstructure 31 and the prism-shaped microstructure 32 on the roller blank B to obtain a composite microstructure roller;
[0062] Q4: Take acrylic resin back coating glue, and prepare hemispherical microstructure 31 and prism-shaped microstructure 32 on the lower surface of the substrate layer 2 by composite microstructure roller and transfer process;
[0063] Q5: Take diffusion particles, acrylic resin, ethyl acetate, butyl acetate, curing agent, and leveling agent in a weight ratio of 0.5:2:3:3:0.2:0.3, mix them, stir them evenly to obtain fine sand glue, and then spray the fine sand glue into the gap between the hemispherical microstructure 31 and the prism-shaped microstructure 32, and then combine the micro-concave scraper coating method to make the diffusion particles evenly distributed in the gap, and obtain the fine sand structure 33 through UV curing or thermal curing, thereby completing the preparation of the back coating 3.
[0064] Preferably, during the UV embossing process in step Q2, the energy of the UV lamp is controlled at 100 mj / cm 2 .
[0065] Preferably, the pyramid-shaped microstructure 32 is one of a quadrangular pyramid, a hexagonal pyramid and an octagonal pyramid.
[0066] Preferably, the diffusion particles are one of PMMA particles, PBMA particles, and acrylic glass beads.
[0067] Preferably, the substrate layer 2 is PET, and the thickness of PET is 250 μm.
[0068] Preferably, the refractive index of the prism layer 1 is 1.55, and the prism structure 11 presents sinusoidal fluctuations along the length direction of the top corner edge, with an amplitude of 1.5 μm.
[0069] Example 3
[0070] A brightness enhancement film that prevents adsorption and improves brightness, comprising, from top to bottom, a prism layer 1, a substrate layer 2, and a back coating layer 3 connected in sequence, the prism layer 1 being provided with a periodically arranged prism structure 11, the back coating layer 3 being evenly distributed with hemispherical microstructures 31, prism-shaped microstructures 32 being provided between adjacent hemispherical microstructures 31, the side surfaces of the prism-shaped microstructures 32 being tangent to the side surfaces of the hemispherical microstructures 31, the height of the prism-shaped microstructures 32 being less than the height of the hemispherical microstructures 31, a gap being left between the prism-shaped microstructures 32 and the hemispherical microstructures 31 and being filled with a fine sand structure 33, the fine sand structure 33 being evenly distributed with diffused particles with a particle size of 4 μm.
[0071] Preferably, the height of the hemispherical microstructure 31 is 18 μm, the height of the prism-shaped microstructure 32 is 11 μm, the width pitch4 of the hemispherical microstructure 31 is 13 μm, the bottom width pitch3 of the prism-shaped microstructure 32 is 8 μm, and the top width pitch2 is 4 μm.
[0072] Preferably, the prism structure 11 is composed of high prisms and low prisms and arranged in a period of high to N low, where N≥1, the height of the high prisms is 32 μm, and the height ratio t of the high prisms to the low prisms is 1<t≤1.25.
[0073] Preferably, N=3, and the pitch pitch1 between adjacent prism structures 11 is 50 μm.
[0074] Preferably, the method comprises the following preparation steps:
[0075] Q1: Take a copper or nickel roller blank A, use a diamond or diamond tool to carve a microstructure texture that matches the one high and three low prism structure on the roller blank A to make a prism roller;
[0076] Q2: Take the substrate layer 2 and the prism glue, and evenly coat the prism glue on the substrate layer 2 by a coating machine, and then combine the prism roller and UV embossing molding to obtain the prism layer 1 on the upper surface of the substrate layer 2;
[0077] Q3: Take a copper or nickel roller blank B, and use a diamond or diamond tool to carve a composite microstructure texture that matches the hemispherical microstructure 31 and the prism-shaped microstructure 32 on the roller blank B to obtain a composite microstructure roller;
[0078] Q4: Take acrylic resin back coating glue, and prepare hemispherical microstructure 31 and prism-shaped microstructure 32 on the lower surface of the substrate layer 2 by composite microstructure roller and transfer process;
[0079] Q5: Take diffusion particles, acrylic resin, ethyl acetate, butyl acetate, curing agent, and leveling agent in a weight ratio of 0.5:1.5:2.5:2.5:0.15:0.25, mix them, stir them evenly to obtain fine sand glue, and then spray the fine sand glue into the gap between the hemispherical microstructure 31 and the prism-shaped microstructure 32, and then combine the micro-concave scraper coating method to make the diffusion particles evenly distributed in the gap, and obtain the fine sand structure 33 by UV curing or thermal curing, thereby completing the preparation of the back coating 3.
[0080] Preferably, during the UV embossing process in step Q2, the energy of the UV lamp is controlled at 75 mj / cm 2 .
[0081] Preferably, the pyramid-shaped microstructure 32 is one of a quadrangular pyramid, a hexagonal pyramid and an octagonal pyramid.
[0082] Preferably, the diffusion particles are one of PMMA particles, PBMA particles, and acrylic glass beads.
[0083] Preferably, the substrate layer 2 is PET, and the thickness of PET is 200 μm.
[0084] Preferably, the refractive index of the prism layer 1 is 1.55, and the prism structure 11 presents sinusoidal fluctuations along the length direction of the top corner edge, with an amplitude of 1.5 μm.
[0085] In conclusion, the above is only a preferred embodiment of the present invention, and all equivalent changes and modifications made within the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A brightness enhancement film that prevents adsorption and improves brightness, comprising, from top to bottom, a prism layer (1), a substrate layer (2), and a back coating layer (3) connected in sequence, characterized in that: The prism layer (1) is provided with a periodically arranged prism structure (11), the back coating layer (3) is uniformly distributed with hemispherical microstructures (31), a prism-shaped microstructure (32) is provided between adjacent hemispherical microstructures (31), the side surface of the prism-shaped microstructure (32) is tangent to the side surface of the hemispherical microstructure (31), the height of the prism-shaped microstructure (32) is smaller than the height of the hemispherical microstructure (31), a gap is left between the prism-shaped microstructure (32) and the hemispherical microstructure (31) and is filled with a fine sand structure (33), and the fine sand structure (33) is uniformly distributed with diffusion particles with a particle size of 3 to 5 μm; The height of the hemispherical microstructure (31) is 15 to 20 μm, the height of the prism-shaped microstructure (32) is 10 to 12 μm, the width pitch4 of the hemispherical microstructure (31) is 10 to 15 μm, the bottom width pitch3 of the prism-shaped microstructure (32) is 6 to 10 μm, and the top width pitch2 is 3 to 5 μm; The prism structure (11) is composed of high prisms and low prisms and is arranged in a period of high N low, N=3, the height of the high prism is 30-35 μm, and the height ratio t of the high prism to the low prism is 1<t≤1.25; The pitch 1 between adjacent prism structures (11) is 45-60 μm; The method comprises the following preparation steps: Q1: Take a copper or nickel roller blank A, use a diamond or diamond tool to carve a microstructure texture that matches the one high and three low prism structure on the roller blank A to make a prism roller; Q2: Take a substrate layer (2) and prism glue, evenly apply the prism glue on the substrate layer (2) by a coating machine, and then combine a prism roller and UV embossing to form a prism layer (1) on the upper surface of the substrate layer (2); Q3: Take a copper or nickel roller blank B, and use a diamond or diamond tool to carve a composite microstructure texture that matches the hemispherical microstructure (31) and the prism-shaped microstructure (32) on the roller blank B to obtain a composite microstructure roller; Q4: Take an acrylic resin back coating and prepare a hemispherical microstructure (31) and a prism-shaped microstructure (32) on the lower surface of the substrate layer (2) by a composite microstructure roller and a transfer process; Q5: Take diffusion particles, acrylic resin, ethyl acetate, butyl acetate, curing agent, and leveling agent in a weight ratio of 0.5:1~2:2~3:2~3:0.1~0.2:0.2~0.3, mix them, stir them evenly to obtain fine sand glue, spray the fine sand glue into the gap between the hemispherical microstructure (31) and the prism-shaped microstructure (32), and then use a micro-concave scraper coating method to evenly distribute the diffusion particles in the gap, and use UV curing or thermal curing to obtain a fine sand structure (33), thereby completing the preparation of the back coating (3).
2. The anti-adsorption and brightness-enhancing film according to claim 1, characterized in that: During the UV embossing process in step Q2, the energy of the UV lamp is controlled at 50~100mj / cm 2 .
3. The anti-adsorption and brightness-enhancing film according to claim 1, characterized in that: The prism-shaped microstructure (32) is one of a quadrangular pyramid, a hexagonal pyramid, and an octagonal pyramid.
4. The anti-adsorption and brightness-enhancing film according to claim 1, characterized in that: The diffusion particles are one of PMMA particles, PBMA particles, and acrylic glass beads.
5. The anti-adsorption and brightness-enhancing film according to claim 1, characterized in that: The substrate layer (2) is PET, and the thickness of PET is 188-250 μm.
6. The anti-adsorption and brightness-enhancing film according to claim 1, characterized in that: The refractive index of the prism layer (1) is 1.55, and the prism structure (11) presents a sinusoidal wave along the length direction of the top corner edge, with an amplitude of 1.5 μm.
Citation Information
Patent Citations
Brightness enhancement film capable of preventing adsorption and improving brightness
CN216792483U